Estudo sobre a necessidade de informação dos integrantes do batalhão de choque da polícia militar do Estado de Goiás - Perucchi, Valmira (2001)
The paper presents results of study done to verify the information need of the military police of the Shock Battalion of the Military Police of the State of Goiás The study was based on the available literature on user studies, specifically on information need. In their daily activities that professional is faced with different situations and needs of relevant information. The complexity and speed with which phenomena occur related to public disorder, and the readiness of the police to present shock solution almost immediately occurred to justify this study on the information needs of these professionals. The quantitative method was used to analyze the data obtained through a questionnaire. Secondly was applied to the interview which sought qualitative analysis of these data. The sample refers to 60 policemen for a population of 98 who were serving in Shock Battalion of the Military Police of Goiás, in the period surveyed: June 2012. In the study it was found that police prefer the use of informal sources of information at the expense of formal sources. The military does not use the grouping studied library and information seekers on the Internet.